Trends in Cervical Cancer Incidence and Mortality in Oklahoma and the United States, 1999-2013 - Gopalani, Sameer Vali (Cancer Epidemiol, 2018)
BACKGROUND: The twin prevention strategies of HPV vaccination and cervical cancer screening reduce new cases and averts deaths, yet women still develop or die from cervical cancer. To assess and better understand the burden of cervical cancer in Oklahoma, we analyzed incidence and mortality trends in Oklahoma from 1999 to 2013. METHODS: We obtained age-adjusted cervical cancer incidence and mortality rates and calculated standardized rate ratios (RR) for women in Oklahoma compared to the US. To evaluate temporal changes in annual age-adjusted incidence and mortality, we calculated the annual percent change (APC) using the Joinpoint Regression Program. RESULTS: We observed higher age-adjusted incidence (RR: 1.2; 95% CI: 1.1, 1.3) and mortality (RR: 1.2; 95% CI: 1.1, 1.2) rates among women in Oklahoma compared to the US. The overall incidence and mortality rates in Oklahoma were 9.7 and 2.9 per 100,000 women, respectively. In Oklahoma, the highest age-adjusted incidence rates were in American Indian/Alaska Native (AI/AN) (14.8 per 100,000 females) and Asian or Pacific Islander (API) (11.7 per 100,000 females) women and the highest mortality rates were in AI/AN (4.5 per 100,000 females) and African American (AA) (3.9 per 100,000 females) women. Incidence rates decreased for AA women (APC: −4.0; 95% CI: −7.7, −0.2), but were stable for all other races and ethnicities in Oklahoma (APC: −0.8; 95% CI: −2.2, 0.7). A stable trend for mortality was observed in Oklahoma (APC: 0.1; 95% CI: −2.2, 2.5) each year. CONCLUSION: Women in Oklahoma had a higher cervical cancer incidence and mortality rate than the US. A disproportionately higher incidence of cervical cancer among AI/AN and API women and deaths among AI/AN and AA women were observed signaling continuing racial disparities.